A Review Of 47 Food Books (See Abstract For Details) - Jaine, Tom (Petits Propos Culinaires, 2007)
Tristram Stuart: The Bloodless Revolution: Radical Vegetarians and the Discovery of India: Harper Press, 2006: ISBN 0007128924: £25. Robert Appelbaum: Aguecheek’s Beef, Belch’s Hiccup, and Other Gastronomic Interjections. Literature, Culture and Food among the Early Moderns: University of Chicago Press, 2006: ISBN 0226021262: £19. Edited by C.M. Woolgar, D. Serjeantson, and T. Waldron: Food in Medieval England: Diet and Nutrition: Oxford University Press, 2006: ISBN 9780199273492: £55. Brian Fagan: Fish on Friday: Basic Books, 2006: ISBN 0465022847: £15.99. Lindsey Bareham: Fish Store: Michael Joseph, 2006: ISBN 0718148096: £20. Simon Courtauld: Food for Thought: Fish and Feather: a Culinary Tour of Britain’s Seas and Skies: Think Books, 2006: ISBN 1845250311: £9.99. Elisabeth Luard: Truffles: Frances Lincoln, 2006: ISBN 0711224935: £20. Warren Belasco: Meals to Come: A History of the Future of Food: University of California, 2006: ISBN 0520241517: £13.95). Heston Blumenthal: In Search of Perfection: Bloomsbury, 2006: ISBN 1408849429: £20. Giorgio Locatelli: Made in Italy Food & Stories: Fourth Estate, 2006: ISBN 1841157015: £27.99. Rose Gray and Ruth Rodgers: Pasta and Ravioli - River Café Pocket Books: Ebury Press, 2006: ISBN 9780091914370: £8.99. Rose Gray and Ruth Rodgers: Salads and Vegetables - River Café Pocket Books: Ebury Press, 2006: ISBN 9780091914387: £8.99. Rose Gray and Ruth Rodgers: Puddings, Cakes and Ice Creams - River Café Pocket Books: Ebury Press, 2006: ISBN 9780091914394: £8.99. Rose Gray and Ruth Rodgers: Fish and Shellfish - River Café Pocket Books: Ebury Press, 2006: ISBN 9780091914363: £8.99. Andrew Whitley: Bread Matters: Fourth Estate, 2006: ISBN 9780007203741: £20. Tom Aikens: Cooking: Ebury Press, 2006: ISBN 0091910013: £25. Laura Mason and Catherine Brown: The Taste of Britain: HarperPress, 2006: £25. Mark Hix: British Regional Food: Quadrille, 2006: ISBN 1844002349: £25. Fuschia Dunlop: Revolutionary Chinese Cookbook: Ebury, 2006: ISBN 0091904838: £25) Andrea Nguyen: Into the Vietnamese Kitchen: Ten Speed Press, 2006: ISBN 1580086659: 35. Simon Parkes and Udit Sarkhel: The Calcutta Kitchen: Mitchell Beazley, 2007: ISBN 9781566566711: £20. Chitrita Banerji: Bengali Cooking: Serif, 2006: ISBN 9781897959503: £9.99. Curry: Dorling Kindersley: £16.99. Dave Myers and Si King: The Hairy Biker’s Cookbook: Michael Joseph, 2006: ISBN 0718149084: £20. Classic One Pot Cooking: Apple Press: £14.99. Najmieh Batmanglij: From Persia to Napa: Wine at the Persian Table: Gazelle Books Ltd, 2006: ISBN 9781933823003: £43.50. Silvena Rowe: Feasts: Food for Sharing from Central and Eastern Europe: Mitchell Beazley, 2006: ISBN 9781845331566: £20. Ursula Ferrigno: Ursula Ferrigno’s Complete Italian Cookery Course: Mitchell Beazley, 2006: ISBN 9781845331924: £20. Jennifer McLagan: Cooking on the Bone: Grub Street, 2006: ISBN 9781904943471: £20. David Everitt-Matthias: Essence, Recipes from Le Champignon Sauvage: Absolute Press, 2006: ISBN 9781904573524: £25. Marco Pierre White: White Slave: Orion, 2006: ISBN 0752874632: £20. Gordon Ramsay: Humble Pie: HarperCollins, 2007: ISBN 9781407401355: £18.99) Jamie Oliver: Cook with Jamie: Penguin, 2006: ISBN 0718147715: £26. Thomasina Miers: Cook: Collins, 2006: ISBN 0007229372: £16.99. Allegra McEvedy: Colour Cookbook: Kyle Cathie, 2006: ISBN 1856266680: £19.99. Ruth Watson: Something for the Weekend, with eight around the table: Quadrille, 2006: ISBN 1844004376: £25. Trish Hilfrety: Gastropub Classics: Absolute, 2006: ISBN 1904573533: £20. Peter Gordon: Vegetables The New Food Heroes: Quadrille, 2006: ISBN 1844003191: £18.99. Sophie Grigson: Vegetables: Collins, 2006: ISBN 0007213778: £25. Gregg Wallace: Veg The Greengrocer’s Cookbook: Mitchell Beazley, 2006: ISBN 9781845332242: £20. Angela Boggiano: Pie: Cassell, 2006: ISBN 9781844035489: £20. Philippa Vanstone: Tarts and Pies: Grub Street, 2006: ISBN 1904943217: £20. Rose Carrarini: Breakfast, Lunch, Tea: Phaidon, 2006: ISBN 0714844659: £19.95. Janet Ross: Leaves from our Tuscan Kitchen: Grub Street, 2006: ISBN 9781904943624: £12.99. Patience Gray and Primrose Boyd: Plats du Jour: Persephone, 2006: ISBN 1903155606: £10. Simon Hopkinson and Lindsey Bareham: The Prawn Cocktail Years: Michael Joseph, 2006: ISBN 0718149807: £25. Cindy Pawlcyn: Big Small Plates: Ten Speed Press, 2006: ISBN 1580085237: £25.